Juridical Review of the Criminal Acts of Economic Exploitation of Children - Nur Ainun; Sriono Sriono; Abdul Hakim (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Exploitation of children is an act that is prohibited by statutory regulations. Several laws and regulations, both the results of ratification of international conventions and laws and regulations issued by Indonesia. This study aims to analyze the criminal sanctions against child exploitation actors in Indonesia. The research method used is the normative juridical method, which is sourced from statutory regulations and literature. The research results show that child exploitation still occurs in Indonesia. The reason for the economic exploitation of children is poverty. The existence of criminal sanctions contained in statutory regulations has not yet provided a deterrent effect for perpetrators of child exploitation. So it is necessary to have the role of the central and local governments in order to reduce child exploitation, namely by enforcing both laws and regional regulations. Law enforcers, especially prosecutors and judges, provide maximum sanctions or threats to perpetrators of child exploitation. Exploitation of child labor will eliminate the existing rights of children such as playing and learning.